MicroRNAs prevent the generation of autoreactive antibodies - Belver, Laura; de Yébenes, Virginia G; Ramiro, Almudena R (Immunity (Cambridge, Mass.), 2010)
MicroRNAs have been shown to be critical for a number of aspects of immune system regulation and function. Here, we have examined the role of microRNAs in terminal B cell differentiation by analyzing Cd19-Cre(ki/+) Dicer1(fl/fl) mice. We found that in the absence of Dicer, the transitional and marginal zone (MZ) B cell compartments were overrepresented and follicular (FO) B cell generation was impaired. microRNA analysis revealed that miR185, a microRNA overexpressed in FO cells, dampened B cell receptor (BCR) signaling through Bruton tyrosine kinase downregulation. Dicer-deficient B cells had a skewed BCR repertoire with hallmarks of autoreactivity, which correlated with high titers of autoreactive antibodies in serum and autoimmune features in females. Together, our results reveal a crucial role for microRNAs in late B cell differentiation and in the establishment of B cell tolerance.